Adaptation of the Marketing Strategies to Customs Requirements in EU Countries - Deineha, Inna; Volkova, Olena; Tyshchenko, Viktoriia; Mohylova, Anastasiia; Zavodovskyi, Stanislav (Theoretical and Practical Research in Economic Fields; Vol 17 No 2 (2026): TPREF Volume XVII Issue 2(38) June 2026DO - 10.14505/tpref.v17.2(38).08, 2026)
The relevance of the study is determined by the growing import volumes, the complexity of customs regulation, and the need to integrate innovative approaches into marketing activities. The aim of the research was to analyse the impact of customs requirements on the choice and adaptation of marketing strategies in EU countries, as well as to investigate their impact on the pricing policy, logistics solutions, and communication channels. The research employed the following methods: statistical data grouping, multifactor analysis, calculation of a weighted average indicator to assess adaptation potential, as well as legal analysis of EU customs norms and regulations. The results of the study showed that the use of global basic competitive growth strategies is the most effective approach to overcoming challenges associated with customs regulation. The practical significance of the research is the provided recommendations for businesses to optimize marketing strategies in accordance with the customs requirements of EU countries. In particular, the tools proposed for effective adaptation can minimize financial risks and increase competitiveness. Further research may focus on the standardization of customs procedures, automation of processes through digital platforms, and analysis of consumer models in EU countries.